VITALITY VANGUARD: INTEGRATIVE STRATEGIES IN NUTRITION AND HEALTHCARE PROFESSIONS - Saleh Melaih S Aldhafeeri, Hana Saleh Bqeel Al Shamiri, Adel Nasser Maroud Saad Al-Dhafiri, Madiha Asim Afins Aldhafeeri, Khalid Ibrahim Khalif Alenazi,; Amal Saleh Buqayl Alshammari, Abdlmageed Ibrahim al-shdaid, Abd Al hadi selman Agll Alshmriy, (Chelonian Research Foundation, 2022)
Healthcare professionals, including nutrition and epidemiology technicians, play a crucial role in delivering high-quality patient care. Effective interprofessional communication and collaboration are essential for optimal patient outcomes and job satisfaction among healthcare workers. This study aims to investigate the relationship between interprofessional communication and job satisfaction among nutrition and epidemiology technicians in Saudi Arabia. A mixed-methods approach was employed, utilizing a cross-sectional survey and open-ended questions. The Interprofessional Collaboration Scale (ICS) and the Job Satisfaction Survey (JSS) were used to assess the levels of interprofessional communication and job satisfaction, respectively. The study also explored the benefits, barriers, and strategies for improving interprofessional communication and job satisfaction in the healthcare setting. The findings revealed moderate to high levels of interprofessional communication and job satisfaction among the participants, with some variations across different healthcare roles and regions. Communication openness, communication with physicians, communication with other healthcare professionals, and healthcare role were identified as significant predictors of job satisfaction. The qualitative analysis highlighted the importance of training and education, promoting a culture of respect and openness, using standardized communication tools, and addressing workload and staffing issues to enhance interprofessional communication and job satisfaction. The study emphasizes the need for interventions and policies that support the well-being and development of nutrition and epidemiology technicians in Saudi Arabia, ultimately leading to improved patient care. Keywords: interprofessional communication, job satisfaction, nutrition technicians, epidemiology technicians, healthcare professionals, Saudi Arabia